2021
DOI: 10.1155/2021/5383210
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of circRNAs in the Regulation of Fetal Development, Muscle Development, and Lactation in Livestock

Abstract: circRNAs are a class of endogenous noncoding RNA molecules with closed loop structures. They are mainly responsible for regulating gene expression in eukaryotic cells. With the emergence of high-throughput RNA sequencing (RNA-Seq) and new types of bioinformatics tools, thousands of circRNAs have been discovered, making circRNA one of the research hotspots. Recent studies have shown that circRNAs play an important regulatory role in the growth, reproduction, and formation of livestock products. They can not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…The chromosome-wise distribution of circRNAs showed that most of the circRNAs originated from chromosome 2 (227), followed by chromosomes 3 (160) and 4 (155) ( Figure 4B ). circRNAs have multiple regulatory roles which can enrich breeding and improve economic traits related to buffalo ( Fu et al, 2018 ; He et al, 2021 ; Yang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromosome-wise distribution of circRNAs showed that most of the circRNAs originated from chromosome 2 (227), followed by chromosomes 3 (160) and 4 (155) ( Figure 4B ). circRNAs have multiple regulatory roles which can enrich breeding and improve economic traits related to buffalo ( Fu et al, 2018 ; He et al, 2021 ; Yang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The miRNAs could be used to find their lncRNAs target; action of miRNAs on lncRNAs could be sequestering them by binding or destroying them by cleaving ( Assmann et al, 2019 ; Xie et al, 2020 ). The tissue-wise extracted circRNAs in the present study could be utilized in the studies of tissue-specific post-transcriptional regulation involving circRNAs and their role in various buffalo diseases ( Gao et al, 2018 ; He et al, 2021 ; Lei et al, 2021 ; Yang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The circRNAs are involved in the physiological activity of animal lactation, and the expression levels of circRNAs vary at different lactation stages (J. Wang, Zhou, et al, 2021). The circRNAs can affect lactation through multiple pathways, such as affecting the proliferation and differentiation of MECs and the expression of fat and protein (He et al, 2021). The regulation of lactation by circRNAs is complex and occurs through multiple pathways.…”
Section: Research On Circrnas In Animal Husbandrymentioning
confidence: 99%
“…Wang, Zhou, et al, 2021). The circRNAs can affect lactation through multiple pathways, such as affecting the proliferation and differentiation of MECs and the expression of fat and protein (He et al, 2021). The regulation of lactation by circRNAs is complex and occurs through multiple pathways.…”
Section: Lactation Traitsmentioning
confidence: 99%
“…The circRNAs are functionally different from miRNA, piRNA and lncRNA, and play an important role as microRNA sponges, regulating gene splicing and transcription, as well as RNA-binding protein sponges and protein/peptide translating (Patop et al, 2019). It also showed close involvement in a series of physiological processes that are regulating fetal growth, muscle formation, and lactation in mammals (Huang et al, 2020;He et al, 2021). CircRNAs are also found to be important in the regulation of post-transcriptional gene expression (Hansen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%